IMPROVING LOCOMOTOR MOVEMENT ABILITY THROUGH THE FOLLOW JUMP GAME - Hidayatullah, Muhammad Afsar; Hafiani, Muhammad; Rasyid, Ivan Nur; Tagap, Bonnaeges Filemonn Sihananto; Anshari, Hafiz; Nashih, Muhammad; Kasanrawali, Andi; Pratiwi, Endang; Normawarni, Halisa (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
This study aims to determine the ability to move the movement through follow jump games for grade 2 education participants aged 7-8 years at SD Negeri Sungai Landas, Banjar Regency, South Kalimantan. The sample and subject studied are the following jumping games. This game was played by grade 2 students of Sungai Landas State Elementary School, Banjar Regency, South Kalimantan with a total of 17 students including 7 boys and 10 girls. This diversion was played by a review of 2 students of Sungai Landas State Elementary School, Banjar Rule, South Kalimantan with a total of 17 students including 7 boys and 10 girls. In this study, the first cycle data was obtained which were very low (0% < a score of ≤ 40%) with a total of 5 students, medium category (40% < a score of ≤ 55%) with a total of 0 students, medium category (55% < a score of ≤ 70%) with a total of 0 students, a high category (70% < a score of ≤ 85%) with a total of 12 students, and a very high category (85% < a score of ≤ 100%) with a total of 0 students. Cycle II states that the very low category (0% < a of score ≤ 40%) with 2 students, the low category (40% < a of  score ≤ 55%) with 0 students, the medium category (55% < a score of ≤ 70%) with 0 students, the high category (70% < a score of ≤ 85%) with 0 students, and the very high category (85% < a score of ≤ 100%) with a total of 15 students. This article proposes the importance of learner movement in physical education learning in play take after follow jump games. Play take after follow jump game includes positive values, having important locomotor movements as a back in performing other, more complex progressions.